IDENTIFIKASI CERITA PADA RELIEF NARATIF DI CANDI SUKUH - Radila Adwina; Agi Ginanjar (JURNAL PANALUNGTIK, 2019)
Candi Sukuh is a sacred temple complex shaped like step-pyramid structure with three terraces, which was used on late period of Majapahit Kingdom, around 15th century. Every terrace is decorated with various reliefs, either ornamental reliefs or narrative reliefs. The tale of the narrative reliefs had been studied by some researchers, but they had different opinion about it. There are also allegations on the tale from those reseachers of some other narrative reliefs, and narrative reliefs that have never been studied before. There are 13 carved stones of those narrative reliefs, with one or more panels on each stone. Each relief may consist of various relief components, such as figures, animals, plants, buildings, weapons, and other things. Those components are compared with other studies of relief on Majapahit period to obtain early identifications of the relief. After that, each component is arranged to form 18 tale scenes. The scenes are compared with Ancient Javanese texts or other sacred building reliefs from Majapahit period, so that the source of the tale and particular scene of the tale are identified.